Pendampingan Pengembangan Kurikulum Muatan Lokal Kalimantan Tengah dalam Kurikulum Merdeka - Hia, Liberti Natalia; Robbani, Hamzah (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2025)
The values, traditions, culture, skills, and concepts that apply in Central Kalimantan must be maintained and preserved through educational activities using the Central Kalimantan local content curriculum, so that they can be passed on to the next generation. The preservation of Central Kalimantan culture in its local content curriculum in the Merdeka Curriculum begins with the preservation of the Dayak language, which is the dominant source of local wisdom, and language is a bridge of local wisdom. Conceptually, implementation of local content in the independent curriculum can be done in three ways, namely: a) by integrating local content into other subjects, b) integrating local content into the theme of the Pancasila profile strengthening project, or c) developing a special local content subject that stands alone as part of the intracurricular program. This paper is motivated by the Education Office's desire to develop a local content curriculum in Central Kalimantan, addressing the needs of schools in the era of the independent curriculum. Using the concepts and philosophy of the independent curriculum, it provides concrete steps and examples for developing a local content curriculum. This program proves that the assistancedevelopment of local content curriculum can provide direct support on local content curriculum, as well as strengthening the role of universities inaccompany the development of the independent curriculum in the era of the Independent Curriculum. The research results show that since the curriculum at the educational unit level, Central Kalimantan has not developed its local content curriculum, so in the era of the independent curriculum, Central Kalimantan needs to develop its local content curriculum.